Wood Waste Turned Into Value Added Products: Thermal Plasticization by Benzylation Process - Birol Üner (University of Zagreb, Faculty of Forestry and Wood Technology, 2017)
Sawdust is usually considered as waste in wood-using industries. These materials can be converted into value added thermoplastics by means of benzylation. Products can be utilized in different applications where plastics are used. Thermoplasticization process was carried out with benzyl chloride under different alkaline conditions, 15, 25 and 35 %, respectively. Alkali ions and concentration affect the substitution reaction. Tailored material structure was remarkably changed. In order to detect changes, crystallinity index of the materials and thermal properties were analyzed. In FTIR spectra, the peaks appeared at 698 cm-1 and 740 cm-1, which indicates the aromatic C-C angular deformation. Multiple peak appears at 3030 cm-1, which indicates benzylation of the materials. The peak increase can be observed at 1596 cm-1 due to the aromatic deformation. Benzyl groups attached to hydroxyl to form ether groups increase the peak intensity. As a result of that, hydrogen bond energy changes and crystallinity of the materials is reduced. This substitution of functional groups changes the decomposition temperature of modified materials. It reduces the decomposition temperature to between 330 and 350 ºC. Thermogravimetric analysis revealed that modified products were characterized by poorer thermal stability compared to raw materials.